Lipid-modulate activity of Cichorium glandulosum Boiss. et Huet polysaccharide in nonalcoholic fatty liver disease larval zebrafish model - Maoru Li; Ji Ma; Owais Ahmad; Yi Cao; Bing Wang; Qiangqiang He; Jiajing Li; Hongli Yin; Yifan Zhang; Jiang He; Jing Shang (Elsevier, 2018)
Nonalcoholic fatty liver disease (NAFLD)1 is the most common chronic liver disease worldwide. Cichorium glandulosum Boiss. et Huet (CG) is a common traditional Uighur medicine, and it has been widely used as active therapy on various hepatic diseases. Recently, lipid-lowering effect has been revealed on CG. Polysaccharides are principal component of CG which could be the possible lipid-lowering compound in CG. In this study, extraction and purification of CG polysaccharides (CGP) was performed, and the lipid regulation effect of CGP was investigated on NAFLD zebrafish model. The results showed that CGP significantly decreased the levels of TC, TG, and decreased the mRNA expression of srebf-1, and fas, increased the expression of pparab. The findings suggest that the lipid-lowering effects of CGP mainly depend on facilitation of lipolysis (mainly beta-oxidation) or inhibition of lipogenesis. Furthermore, CGP could prevent and causes the regression of steatosis in NAFLD via its lipid metabolism regulation effect. Keywords: Cichorium glandulosum Boiss. et Huet, Polysaccharides, Non-alcoholic fatty liver disease, Lipid-lowering, Zebrafish